2008
DOI: 10.1021/jf703689u
|View full text |Cite
|
Sign up to set email alerts
|

Study of Some Physicochemical and Functional Properties of Quinoa (Chenopodium Quinoa Willd) Protein Isolates

Abstract: The amino acid composition and the physicochemical and functional properties of quinoa protein isolates were evaluated. Protein isolates were prepared from quinoa seed by alkaline solubilization (at pH 9, called Q9, and at pH 11, called Q11) followed by isoelectric precipitation and spray drying. Q9 and Q11 had high levels of essential amino acids, with high levels of lysine. Both isolates showed similar patterns in native/SDS-PAGE and SEM. The pH effect on fluorescence measurements showed decreasing fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
181
5
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(221 citation statements)
references
References 36 publications
27
181
5
8
Order By: Relevance
“…Ranhotra et al (1993) also concluded that the quality of protein in quinoa equals that of casein. Both quinoa and amaranth are consistent in their nutritive value for a fact that their protein content is very similar and comparable to the whole milk protein casein (Escudero et al 2004;Abugoch et al 2008;James and Lilian 2009). They also contain good amount of dietary fiber, which are known to affect satiety by their water retaining capacity.…”
Section: Introductionmentioning
confidence: 86%
“…Ranhotra et al (1993) also concluded that the quality of protein in quinoa equals that of casein. Both quinoa and amaranth are consistent in their nutritive value for a fact that their protein content is very similar and comparable to the whole milk protein casein (Escudero et al 2004;Abugoch et al 2008;James and Lilian 2009). They also contain good amount of dietary fiber, which are known to affect satiety by their water retaining capacity.…”
Section: Introductionmentioning
confidence: 86%
“…To stimulate more extensive use and create added value of (sweet) quinoa in the production of foods, ingredients derived from quinoa by fractionation have been explored by several studies, in particular, the production of protein isolates (Brinegar and Goundan 1993;Brinegar et al 1996;Chauhan et al 1999;Aluko and Monu 2003;Lindeboom 2005;Abugoch et al 2008;Aora and Alvarado 2009;Valenzuela et al 2013;Föste et al 2015;Avila Ruiz et al 2016a, b). In all these studies, the conventional wet fractionation method was applied.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have compared the physicochemical and functional properties of buckwheat protein, soya protein isolate and casein (5,6,8). The functional characteristics of pseudocereals as quinoa and amaranth have also been reported in literature (5,9,10). Regarding cereals and other oilseeds, some authors have made comparisons among the protein functional properties of rice cultivars, peanut fl our and peanut protein concentrate as indicators of their potential use in food industry (11,12).…”
Section: Introductionmentioning
confidence: 99%